2018
DOI: 10.1055/s-0037-1603460
|View full text |Cite
|
Sign up to set email alerts
|

Multi-institutional Analysis of Surgical Management and Outcomes of Mandibular Fracture Repair in Adults

Abstract: Mandibular fractures are rare, most commonly occurring in young male patients who present with facial trauma. The etiology, incidence, and presentation vary among previous publications depending on cultural and socioeconomic factors of the region of origin. This multi-institutional study aims to present demographic characteristics, surgical treatment, and clinical outcomes of surgical repair of mandible fractures in the United States. An analysis of the American College of Surgeons National Surgical Quality Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 25 publications
(69 reference statements)
5
16
0
Order By: Relevance
“…An European multicenter study reported ORIF as the most common treatment, 24 in the present study, we similarly reported an operative rate of 75.6% and the remaining 24.4% were managed conservatively with serial reviews. Other studies generally reported similar operative rates, Gulateri's Italian study identified young males commonly presented with condylar fractures and had a total operative rate of 66.9% 25 .…”
Section: Discussionsupporting
confidence: 80%
“…An European multicenter study reported ORIF as the most common treatment, 24 in the present study, we similarly reported an operative rate of 75.6% and the remaining 24.4% were managed conservatively with serial reviews. Other studies generally reported similar operative rates, Gulateri's Italian study identified young males commonly presented with condylar fractures and had a total operative rate of 66.9% 25 .…”
Section: Discussionsupporting
confidence: 80%
“…[9][10][11] In addition, diabetes mellitus has been identified as a risk factor for complications following facial fracture repair in a study using the Nationwide Inpatient Sample database. 13 While ASA classification has been shown to be associated with rates medical complications after mandible fracture repair, 14 there has been to our knowledge, no prior study that explores the specific associations between ASA classification and complications following other facial fracture repairs. It has been well established that ASA class can help predict operative risk of morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Increased times to treatment can encompass a number of different factors, including concomitant injuries taking precedence, admission to ICU, surgeon or operating room availability (particularly for complex and time-consuming cases), and transfer from a community hospital. 15,19,20 These factors did not influence the complication rates in the present study as most of them were controlled. From previous experience in the study environment, the time for surgical repair is also affected by financial constraints and ignorance of some patients on where to get the best care as the facility where this study was done is one of the few health institutions in Nigeria designated for the treatment of such cases.…”
Section: Ta B L E 1 Distribution Of Demography Of the Patients And Et...mentioning
confidence: 61%